Forces of secularity in the modern world / volume 1 - Strehle, Stephen (Forces of secularity in the Modern World, 2018)
The spiritual crisis of early capitalism -- The rise of acquisitive capitalism -- The development of acquisitive capitalism and social Darwinism in Britain -- The removal of religion from human development and natural events -- Enlightened history -- The mechanistic universe -- Innocent suffering -- The marginalization of the church in American society as a private matter -- Mr. Jefferson -- The development of the wall